The Educational Policy for The Development of The Early Childhood Education Curriculum at The Kunming Preschool Teachers' Training College, Yunnan Province, People's Republic of China, which Focuses on Producing Competent Teachers for Professional Practice in Thailand - Chao, Peng; Wang-on, Gomin; Bunnun, Vikrom; Muangkasem, Banjamas (Dhammathas Academic Journal, 2024)
The purposes of this research were 1) to analyze the competencies and capabilities of Chinese teachers teaching early childhood education in Thailand, 2) to study approaches for developing early childhood education curricula, and 3) to provide educational policy recommendations for developing early childhood education curricula focused on producing competent teachers for professional practice in Thailand, specifically for the Kunming Preschool Teachers' Training College, Yunnan Province, People's Republic of China. It is a mixed-methods research combining quantitative and qualitative approaches. The research tools included a questionnaire for 15 Chinese teachers teaching early childhood education in educational institutions, semi-structured interviews with 16 representatives from educational organizations in Thailand and China, and content analysis of the results from objectives 1 and 2 to provide policy recommendations. The results revealed that: 1. The overall capability of Chinese teachers was rated as low, and the overall competency in teaching was rated as moderate. The area with the highest average was positive interaction, followed by promoting children's development, which also showed moderate competency. 2. Proposed strategies for developing the early childhood education curriculum included improving the curriculum to motivate students to pursue teaching careers in Thailand, adding courses related to teaching Chinese as a foreign language, enhancing the competencies of Chinese teachers, and fostering educational collaboration. 3. The educational policies for developing early childhood education curricula to produce competent teachers for professional practice in Thailand consisted of 1) a policy for developing early childhood education curricula focused on producing competent teachers in teaching Chinese, adding courses and essential skills; 2) a policy for developing the competencies of early childhood education students by improving their capabilities and competencies for the workforce; and 3) a policy for fostering collaboration between educational institutions in Thailand and China through student and faculty exchanges, research, and collaborative curriculum development between institutions.